The influence of mindful leadership and organizational culture on organizational commitment with self-efficacy as an intervening variable - Nugraha, Mochammad Hilmi; Badruzaman, Jajang; Rusliana, Nanang (MBR (Management and Business Review), 2024)
The study aims to determine the effect of mindful leadership, organizational culture on organizational commitment with self-efficacy as an intervening variable. The total sample in the study was 266 respondents, the analytical tool used to test the hypothesis was Path Analysis. Based on the results of the study from the responses given by East Priangan region private university lecturers, it is known that mindful leadership and organizational culture indirectly influence organizational commitment through self-efficacy.